IRAN-EURASIANECONOMIC UNION AGREEMENT FROM THE PERSPECTIVE OF GEO-ECONOMIC CONSEQUENCES - H. M. Seyed (Современная наука и инновации, 2022)
The signing of the agreement on the establishment of a free trade zone between the Islamic Republic of Iran and the Eurasian Economic Union can be considered a very important turning point in the post-Soviet interactions between Iran and the Eurasian region.